An Interactive Augmented and Virtual Reality System for Managing Dental Anxiety among Young Patients: A Pilot Study - Reham Alabduljabbar; Maha Almutawa; Renad Alkathiri; Abeer Alqahtani; Hala Alshamlan (Applied Sciences, 2023)
Dental anxiety is a common health problem among children. It creates major issues for patients, parents, and dental professionals. Children who cancel or otherwise miss their dental appointments generally do so due to fear of the unknown and lack of understanding of what they can expect from the environment and treatment when they arrive there. Some distraction interventions are already used by dental professionals, such as using clown doctors, watching cartoons, and utilizing the tell–show–do (TSD) technique. Still, the problem is common, and the fail to attend (FTA) rates at clinics are high. Familiarizing children with the dental setting and procedures in advance may help to manage their anxiety. This paper aims to help in managing children’s dental anxiety in a simple, attractive, and age-appropriate way through the use of augmented reality (AR) and virtual reality (VR) technologies. The developed system is named “Dr. Barea”. It targets Arabic-speaking children aged from 7 to 10 years old. It uses model–view–control (MVC) as its architectural design pattern. The proposed solution consists of three main sections: a 360° VR video that simulates a dental clinic environment, an educational description on dental tools using AR technology, and interactive educational stories that educate children about dental hygiene. The system performance was evaluated using unit, integration, performance, and user acceptance testing. The results demonstrate that the proposed solution, which performed reasonably, achieved the usability requirements and was engaging for learning information about dental hygiene. A feasibility study with 16 children was conducted to evaluate the effectiveness of the proposed system. The Child Fear Survey Schedule—Dental Subscale (CFSS-DS) was used to measure children’s dental anxiety level. The T test was used to evaluate the differences between groups, and Fisher’s exact test was used to compare the distributions of gender and age between the groups. The CFSS-DS index in the VR group decreased after dental consultation (35.04 ± 9.14 before consultation and 32.32 ± 8.32 after consultation, p = 0.041). The implications of this study shall be beneficial to patients, parents, and dental professionals.